Penggunaan Bahasa Formal dan Informal dalam kehidupan sehari-hari pada Mahasiswa Fakultas Pendidikan Universitas Negeri Medan - Dewi Nuriani Balqissyah; Debi Ester Claudia Siregar; Amnah Khairani; Saufina Azzahra Zebua; Dhiya Faliha Syahira; Rosmini Rosmini (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Language is humanity's primary tool for communication, enabling the exchange of ideas, feelings, and ideas between individuals in social and academic contexts. The use of formal and informal language by students is an important topic in the educational context, especially for Faculty of Education students who will become teaching staff in the future. This research aims to analyze the use of formal and informal language in the daily lives of students at the Faculty of Education, Medan State University, and understand the importance of mastering these two types of language in their role as prospective educators. Using a questionnaire method distributed to 47 respondents, the research results showed that students tend to use informal language in everyday social interactions, while formal language is more dominantly used in academic situations. However, there are difficulties in maintaining consistent use of formal language in academic environments due to the influence of social media and informal habits in everyday life. This research highlights the need for a deeper understanding of the use of language appropriate to the context, both formal and informal, in order to improve students' communication skills in their role as prospective educators.